Determinants of Libyan National Interests in Light of National Security Theory: A Study of Sovereign, Institutional, and Societal Dimensions (Al-Farooq Journal of Sciences, 2026)
In light of the profound transformations taking place in the Libyan state, the issue of defining national interests has become one of the central concerns associated with state reconstruction and the achievement of stability. Within this context, this study seeks to approach Libyan national interests from the perspective of comprehensive national security. Thus, the core problem of the study revolves around the main question: What are the key determinants of Libyan national interests in light of national security theory? The study aims to identify the sovereign and geopolitical determinants of Libyan national interests, as well as to clarify the institutional, economic, and social determinants of these interests within the framework of comprehensive national security. It employs both descriptive and analytical methodologies to describe and analyze the theoretical concepts related to national security and national interests. The study concludes with significant findings, indicating that the Libyan situation illustrates the limitations of the traditional approach to national security, highlighting the necessity of adopting a comprehensive national security concept that integrates political, economic, and social dimensions.
Keywords: Determinants, national interests, Libya, Theory, National Security.